Effectiveness of External Precooling and Vibration Induced by BUZZY on Pain and Anxiety During Inferior Alveolar Nerve Block Injection in Children - Reyhane Narimany; Reyhaneh Faghihian; Mehdi Jafarzadeh Samani (International Journal of Dentistry)
Conclusion: Under the limitations of the present study, a combination of precooling and vibration using the BUZZY device did not decrease pain and anxiety in children during the IANB injection.